(untitled) (Economics and region, 2018)
The article presents an overview of the development of trends in labor market changes in the context of the development of unregulated internal migration processes. The logistic interpretation of the labor market and the impact of the migration process on the basis of analytical modeling with the use of mathematical tools for formalization of processes are given. The necessity of development of infrastructure support of the labor market for the purpose of liquidation of imbalance is substantiated. The basis of effective regulation of the labor market is the introduction of optimal parameters for the development of the labor market and its infrastructure support. The proposed mechanism of logistics of the processes of influencing the migration of the population to the state of work and staffing needs of the economic system of the national economy is a necessary condition for determining the optimal parameters of the labor market development of components, which maximizes the effectiveness of market regulation measures.